Influence of Leaf Area Index and Plant Height on Green Roof Carbon Footprint in Moroccan Residential Buildings in Hot Climates - Idouanaou Abdessamad; Malha Mustapha; Bah Abdellah; Kardellass Saïd (EPJ Web of Conferences)
Green roofs are a sustainable solution to reduce energy consumption and carbon footprints, especially in hot climates. This study investigates the influence of two key design parameters, Leaf Area Index (LAI) and plant height, on the thermal performance and carbon footprint of residential buildings in Morocco. Using advanced simulation techniques, the study evaluates the impact of these parameters on electricity consumption for heating and cooling. The results show that increasing LAI and plant height reduces cooling-related CO₂ emissions by up to 3.87%, with taller plants and denser vegetation improving shading and evapotranspiration. However, during heating days, these parameters increase CO₂ emissions by up to 13.12%, due to reduced solar heat gain. Annual CO₂ emissions are reduced by approximately 1.13% when green roofs with optimized vegetation are implemented. The findings highlight the need for season specific maintenance practices, such as watering green roofs during cooling seasons and trimming vegetation during heating seasons, to balance energy performance. This study provides practical recommendations for optimizing green roof designs to support Morocco’s climate goals and sustainable urban development.